Effect of types of stimuli, handedness and gender differences on reaction time among adults students during the COVID-19 pandemic - Bari Dindar S.; Yacoob Aldosky Haval Y. (Biomedical Human Kinetics, 2022)
Study aim: The COVID-19 pandemic has unhinged the lives of people across the globe, in particular, university students who are home-schooling. No study has investigated the influence of specific parameters on reaction time (RT) among university students during the COVID-19 pandemic. The current study aims to describe the relationship between RT and parameters (types of stimuli, handedness, and gender differences) that may affect its values during the COVID-19 pandemic.